En bloc resection, is this the future of non-muscle invasive bladder cancer management? Presentation of our technique and brief review of the literature. Issue 1 (February 2023) - Symeonidis, Evangelos N; Baniotis, Panagiotis; Langas, Georgios; Stefanidis, Panagiotis; Tsiakaras, Stavros; Stratis, Michail; Savvides, Eliophotos; Bouchalakis, Athanasios; Petras, Stefanos; Memmos, Dimitrios; Anastasiadis, Anastasios; Mykoniatis, Ioannis; et al.
Introduction: The quality of the initial transurethral resection of bladder tumors (TURBT) plays a key role in accurate local staging thus affecting treatment decision-making and disease prognosis. TURBT is still the gold standard for non-muscle invasive bladder cancer (NMIBC). However, en bloc resection of bladder tumors (ERBT) gradually expanded as a promising alternative to TURBT, aiming to overcome certain inherent limitations of conventional resection. We hereby describe a step-by-step bipolar ERBT technique and briefly review the current trends surrounding the role of various en bloc techniques in the field. Case presentation: We present the case of a 65-year old patient undergoing bipolar ERBT for a single, approximately 2 cm, papillary bladder mass. An experienced urologist completed the procedure within 17 min and without any intra- or postoperative complications. No conversion to TURBT was needed, and an adequate specimen for histological assessment was obtained. The patient made an uneventful recovery, and no recurrence was noted at 12-months. Conclusion: Our initial experience demonstrates that ERBT via bipolar current is relatively quick, safe, and reliable. Prospective comparative clinical trials will examine its efficacy, and long-term oncological superiority in managing NMIBC.